Cystic fibrosis in the era of precision medicine. (January 2018) - Paranjape, Shruti M.; Mogayzel, Peter J.
Summary: The treatment of people with cystic fibrosis (CF) has been transformed by the availability of drugs that target the basic chloride defect in the disease. The use of drugs that target specific molecular defects embodies the goals of precision medicine, which incorporate preventive and therapeutic strategies and takes into account differences among individuals. However, the entirety of CF care, from diagnosis to understanding the clinical phenotype and developing a therapeutic strategy, depends on taking into account individual characteristics to achieve optimal outcomes. Future therapies are likely to be even more individualized ushering in a new era of precision medicine.